A Textbook to Help Students Think Like MicrobiologistsReview of: <source>Microbiology</source>, <edition>1st ed.</edition>; <person-group person-group-type="editor"> <name name-style="western"> <surname>Wessner</surname> <given-names>David R.</given-names> </name> <name name-style="western"> <surname>Dupont</surname> <given-names>Christine</given-names> </name> <name name-style="western"> <surname>Charles</surname> <given-names>Trevor C.</given-names> </name> </person-group>; ( <year>2013</year>). <publisher-name>John Wiley & Sons, Inc.</publisher-name>, <publisher-loc>Hoboken, New Jersey</publisher-loc>. <fpage>960</fpage> pages. - Lianna Etchberger (American Society for Microbiology, 2013)
Review of: Microbiology, 1st ed.; David R. Wessner, Christine Dupont, and Trevor C. Charles; (2013). John Wiley & Sons, Inc., Hoboken, New Jersey. 960 pages.